Comparative Study on Residents' Health-Promoting Lifestyle and Life Satisfaction in Wuhan Before and After the COVID-19 Pandemic - Da Ke; Wei Chen (Frontiers Media S.A., 2022)
The Coronavirus Disease-19 (COVID-19) pandemic has dramatically affected residents' life. Whether the COVID-19 pandemic has significantly influenced the residents' health-promoting lifestyle, and life satisfaction is an urgent problem to be studied. Based on Health Belief Model (HBM), this paper explored and compared the responses of residents' health-promoting lifestyle and life satisfaction on the influence of the COVID-19 pandemic. Data were collected from a sample of 2,054 residents in Wuhan by questionnaire survey. The results show that the total score of health-promoting lifestyle after the COVID-19 pandemic has increased significantly compared with that before the COVID-19 pandemic, and the scores of all dimensions of health-promoting lifestyle have improved. Among them, the scores of exercises, self-actualization, and stress management are significantly higher than those before the COVID-19 pandemic. However, the score of residents' life satisfaction has shown a downward trend. There were also significant differences in life satisfaction on the demographic variables, such as gender, age, education level, marital status, and family average income. The findings are of great significance in promoting residents' health-promoting lifestyles and life satisfaction in the context of the extraordinary pandemic.